2022
DOI: 10.14488/bjopm.2022.007
|View full text |Cite
|
Sign up to set email alerts
|

Training for Industry 4.0: a systematic literature review and directions for future research

Abstract: Goal: This study aims to identify, synthesize and classify the main features explored by current research encompassing training for Industry 4.0 and propose directions for future research. Design / Methodology / Approach: The methodological procedure was oriented by a systematic literature review (PRISMA) methodology and followed by content analysis. After a review of academic databases, 78 papers dealing with training for Industry 4.0 were included and classified based on topics related to the science of trai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…While studying the readiness for Industry 4.0 of SMEs' (Stentoft et al, 2021) addressed the deficiency of knowledge of managers about drivers and barriers of I4.0 as an obstacle. Because managers have to navigate the transition to Industry 4.0 by developing the appropriate goals, culture, and relationships (Cazeri et al, 2022). Moktadir et al (2018) identified "a lack of technological infrastructure" as the main challenge for Bangladesh's leather industry to implement Industry 4.0 and proposed revamping strategic approaches for a reconfiguring production system.…”
Section: Literature Reviewmentioning
confidence: 99%
“…While studying the readiness for Industry 4.0 of SMEs' (Stentoft et al, 2021) addressed the deficiency of knowledge of managers about drivers and barriers of I4.0 as an obstacle. Because managers have to navigate the transition to Industry 4.0 by developing the appropriate goals, culture, and relationships (Cazeri et al, 2022). Moktadir et al (2018) identified "a lack of technological infrastructure" as the main challenge for Bangladesh's leather industry to implement Industry 4.0 and proposed revamping strategic approaches for a reconfiguring production system.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Despite the advantages technology brings, it can have barriers to its implementation, such as resistance to change, the lack of a clear direction from leadership, the scarcity of qualified workforce and the need for training and reliable educational programs (Jain et al 2021;Bakhtari et al 2021). Previous research has shown that companies are affected by the lack of information on how to keep pace with modern technology (Cazeri et al 2022), and the business environment is in need of digital skills, with a proactive approach in training the existing and future employees (Flores et al 2018;Hamada 2019;Mahlmann Kipper et al 2021;Saniuk et al 2021), as well as involving customers in the design and planning of new technological products, services or environments (Amendola et al 2018). HEIs could support this endeavor.…”
Section: Contextmentioning
confidence: 99%
“…Given the context presented, this paper aims to analyze competence management practices performed by Brazilian industries. A scarcity of research on competence management in Brazil was noted based on the assessment of the existing literature (Cazeri et al, 2022;Pio et al, 2022;Rampasso et al, 2021), leading to the decision to conduct an exploratory study without restricting it to a specific sector in order to gain a more comprehensive understanding of the industrial context in this country. A survey was conducted with experts who assessed 13 practices (P) elaborated based on the guidelines of ISO 10015:2020, considering two categories: large industries (LI) and small and medium-sized industries (SMI).…”
Section: Introductionmentioning
confidence: 99%
“…Given the context presented, this paper aims to analyze competence management practices performed by Brazilian industries. A scarcity of research on competence management in Brazil was noted based on the assessment of the existing literature (Cazeri et al. , 2022; Pio et al.…”
Section: Introductionmentioning
confidence: 99%